Dendeng Kak Su / Muhammad Fadhil Ahmad - Ahmad, Muhammad Fadhil (2021)
“Kongsikan Keenakkan Bersama” is a tagline for Dendeng Kak Su page business that represent to our beloved customers. Dendeng Kak Su's major goal is to develop products that are accessible to a wide range of consumers while steadily increasing our profit margins. Another goal is to ensure that our products and services are of excellent quality, since this is one method to assist our customers appreciate and believe in what we have to offer. On April 10th, 2021, we launched our internet company on the social media platform. People who desire something good but not too expensive are our target market. We've received a lot of positive feedback from new and old customers about the quality of our excellent meat since our first grand teaser opened. Furthermore, we provided free delivery and mailing to individuals who lived in close proximity to our location. Dendeng Kak Su goods have a unique selling proposition (USP) that allows our business to focus on overall consumer and customer perceived value of our unique advantage shown by our service, product, and brand, allowing it to stand out from other rivals by competing on quality. Dendeng Kak Su products were sold in large quantities, with a total of fifteen packages sold. Dendeng Kak Su has shown to be an excellent choice with a high-quality product at an inexpensive price that will thrive in Malaysia and beyond.